Experimental and Numerical Research on Steel Plate Shear Wall with Infill Plate Connected to Beam Only - Amirhosein Raisszadeh; Ardeshir Deylami; Alireza Rahai (Salehan Institute of Higher Education, 2018)
Steel plate shear walls consist of thin infill steel plates attached to beams, called (horizontal boundary elements, HBEs), and columns (vertical boundary elements, VBEs) in structural steel frames. The thin unstiffened web plates are expected to buckle in shear at low load levels and develop tension field action, providing ductility and energy dissipation through tension yielding of the web plate. HBEs are designed for stiffness and strength requirements and are expected to anchor the tension field formation in the web plates. VBEs are designed for yielding of web plates and plastic hinge formation at the ends of the HBEs. This design approach may result in very large demand on boundary frame members, especially VBEs in most cases. Several methods such as using LYP, perforating the infill plate and omitting connection of infill plate to columns have been proposed to reduce the moment and axial force demands on the VBEs. Study the behavior of steel plate shear walls omitting the connection of infill plate and columns is the main purpose of this research. A classic analysis base on PFI method along with quasi static cyclic experimental study has been performed in order to investigate the behavior of such a system. The results of the experimental study are used to verify numerical models. Behaviors of proposed system (overall capacity and initial stiffness) were compared with those of the conventional SPSWs. Results show that both parameters are reduced in comparison to the conventional SPSWs.